2023
DOI: 10.1002/pc.27256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkaline treatment on physical, structural, mechanical and thermal properties of Bambusa tulda (Northeast Indian species) based sustainable green composites

Abstract: In recent years, sustainable composites have gained increased attention due to various reasons, such as the depletion of non‐renewable resources, environmental sustainability, and the introduction of plastic pollution. The present work aims to develop biocomposites (with a maximum biological content of 61.78%) based on Bambusa tulda fiber and cashew‐nut shell oil‐based bio‐epoxy resin. Different concentrations of NaOH (2%, 4%, 6%, 8%, and 10%) are used to determine the most suitable NaOH concentration for bamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 59 publications
(91 reference statements)
0
15
0
Order By: Relevance
“…Previous studies reported the development of biobased epoxy resins by replacing the traditional building blocks of epoxy polymer with biomass derivatives: such as vegetable oil, [5,6] cardanol, [7][8][9][10] furan, [11] rosin, [12] and lignin. [13][14][15][16][17] Plant-derived reinforcements (natural fibers) with petroleum-based epoxy resins have been extensively studied and commercialized in the last few decades.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported the development of biobased epoxy resins by replacing the traditional building blocks of epoxy polymer with biomass derivatives: such as vegetable oil, [5,6] cardanol, [7][8][9][10] furan, [11] rosin, [12] and lignin. [13][14][15][16][17] Plant-derived reinforcements (natural fibers) with petroleum-based epoxy resins have been extensively studied and commercialized in the last few decades.…”
mentioning
confidence: 99%
“…[20] Natural fibers are hydrophilic and possess poor wettability with commercial epoxy; therefore, they are often physically or chemically modified to improve these properties. [10,41,42,44] Bamboo fiber is an ideal candidate among natural fibers due to its availability, fast growth, excellent mechanical properties, and durability. [10,42,43] Previous studies reported fabricating "partially" biobased composites using commercial epoxies with 40-50% biocontent and plant fibers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The primary issue with plastic now-a-days is that, most of it is non-degradable, and this undeterred litter on the surface of the earth not only threatens marine and human life but also pollutes the air, soil, and water. [1][2][3][4][5] Natural fiber reinforced composite has drawn a lot of interest recently since it uses fiber sources that are environment-friendly. Their processing and handling are simpler and need less expenditure than those of made up of conventional sources.…”
Section: Introductionmentioning
confidence: 99%